GG's and NT's: Gaming language in the chat feature of FPS game Valorant - Susanti, Allycia (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2022)
Language plays a significant role in gaming. First-person shooting (FPS) video game players need to communicate with each other to coordinate and progress in the game. However, there is still a big gap in research regarding language use in gaming outside the scope of language learning and acquisition. Thus, this research paper analyses the way Valorant players communicate with each other via text messages during matches. Conversations that took place during five matches are retrieved from the built-in text communication feature so that the strategies and patterns of communication utilised by Valorant players can be observed. A short interview involving a few random players from the five games was also conducted to retrieve more data regarding the strategies and patterns of communication utilised by Valorant players. The findings suggest that not only do video game players often choose not to conform to existing grammatical and lexical rules, they also utilise vocabularies that only make sense in the scope of the game. In other words, linguistic deviations and neologism by giving existing words new meanings often occur in gaming language.Keywords: Valorant, strategies, patterns, gaming language